1984
DOI: 10.1002/ar.1092100113
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial fusion during early semicircular canal formation in the embryonic zebrafish, Brachydanio rerio

Abstract: The developing inner ear of the teleost, Brachydanio rerio, provides an opportunity for observing an epithelial fusion between the apical surfaces of apposed epithelia in a vertebrate embryo in vivo. The developing otocyst was filmed for periods up to 4 days in unanesthetized embryos, and specimens were fixed at intervals and processed for light microscopy, TEM, and SEM. The semicircular canals are formed as a consequence of the union between the tips of three cylindrical projections from the wall of the otocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 14 publications
3
64
1
Order By: Relevance
“…3G,H, lateral and medial views). The process of canal formation is roughly similar in other vertebrates, with pillars (zebrafish) or plates (birds and mammals) joining centrally to demarcate the canals (Knowlton, 1967;Waterman and Bell, 1984;Martin and Swanson, 1993;Haddon and Lewis, 1996). In the early stage 47 paintfilled specimens, the canals are distinct from the utricle but still tightly apposed to its surface.…”
Section: Stages 47-52mentioning
confidence: 92%
“…3G,H, lateral and medial views). The process of canal formation is roughly similar in other vertebrates, with pillars (zebrafish) or plates (birds and mammals) joining centrally to demarcate the canals (Knowlton, 1967;Waterman and Bell, 1984;Martin and Swanson, 1993;Haddon and Lewis, 1996). In the early stage 47 paintfilled specimens, the canals are distinct from the utricle but still tightly apposed to its surface.…”
Section: Stages 47-52mentioning
confidence: 92%
“…Compared with mammals (see a review by Rübsamen and Lippe 1998), the zebrafish is a unique model for the study of early development of hearing and balance in vertebrates because the inner ear of zebrafish embryos is easily accessible for live imaging, physiological recording, and genetic manipulation (Waterman and Bell 1984;Haddon and Lewis 1996;Nicolson et al 1998;Bever and Fekete 2002;Whitfield 2002;Nicolson 2005;Zeddies and Fay 2005;Tanimoto et al 2011). Previous studies have reported on the development of auditory sensitivity in a few juvenile and adult teleosts using various physiological methods (Corwin 1983;Kenyon 1996;Higgs et al 2003;Sisneros and Bass 2005;Vasconcelos and Ladich 2008;Alderks and Sisneros 2011;Lechner et al 2012).…”
Section: Development Of Structure and Function Of The Inner Earmentioning
confidence: 99%
“…Semicircular canal formation involves a complex reshaping of the ear epithelium, and has been described in detail in the zebrafish by Waterman and Bell (1984). No initial flattened pouch of presumptive semicircular canal tissue is seen, in contrast to the amniote ear .…”
Section: Development Of Semicircular Canalsmentioning
confidence: 99%
“…The lateral projection later forms three bulges, pointing rostrally, caudally, and ventrally; these eventually contact the rostral, caudal, and ventral projections, respectively, forming fusion plates at the points of contact. Rearrangement of the epithelium here generates a continuous tube or pillar; cell death does not seem to be prevalent at the fusion plate (Waterman and Bell, 1984). The pillar can then be thought of as the hub of the developing semicircular canal, the canal itself being the fluid-filled toroidal space surrounding each hub.…”
Section: Development Of Semicircular Canalsmentioning
confidence: 99%